2019
DOI: 10.20944/preprints201902.0124.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ligand-Protein Interactions: A Hybrid ab initio/Molecular Mechanics Computational Study

Abstract: The enzymes Cyclooxygenase (COX) or prostaglandin-endoperoxide synthase (PTGS) are important in the synthesis of prostaglandins, which are the main mediating chemi- cals at inflammatory processes. The body produces two highly homologous COX isoforms, cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2). COX-1 is involved in the pro- duction of prostaglandins which take part in physiological processes such as: protection of the gastric epithelium, maintenance of renal flow, platelet aggregation, neutrophil mi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Compare to affinity character between chlorogenic acid and COX-2 in this research indicated that interaction was blocking at COX-2 in different active site location compare to other ligand complexes COX-2 NSAID (Perez et al, 2019). Different binding sides in COX-2 have potential role for inhibiting COX-2 function in different effects compare to chemical drugs.…”
Section: Resultsmentioning
confidence: 62%
“…Compare to affinity character between chlorogenic acid and COX-2 in this research indicated that interaction was blocking at COX-2 in different active site location compare to other ligand complexes COX-2 NSAID (Perez et al, 2019). Different binding sides in COX-2 have potential role for inhibiting COX-2 function in different effects compare to chemical drugs.…”
Section: Resultsmentioning
confidence: 62%